الثورات العربية المعاصرة في ميزان الفقه الإسلامي: دراسة تحليلية تأصيلية - بهيويا، محمد إبراهيم خليل (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
People in the Muslim world are trying to politically transform tyranny to freedom, and arbitration of dictatorship to return to the Islamic Constitution. Due to this, a lot of contemporary revolutions have been formed in the Arab and Islamic world, especially in the Middle East. Therefore, this study highlights the concept of revolution, its causes, cases of the most famous revolutions in Islamic history and its provisions from the Islamic point of view. The researcher adopted the inductive method by taking a collection of different words about the legality of the revolution, and by referring to the original sources of books and papers published to date, and by denoting to the websites pertinent to the revolutions. The author also used the analytical method for the analysis of the views and their compatibility with the perceived reality and observations of the nation's needs (مقاصد) and purposes of the Islamic Law. The study found that the inadmissibility of the armed revolution against the Muslim rulers to disseminate the rising chaos and the existing corruption in the country is not permissible. It has been forbidden by Islam as it causes destruction to the earth and the disobedience to the Muslim rulers simultaneously gives rise to more chaotic situations rather than solve the problems. But peaceful revolution can be considered if the terms and conditions of the revolution are fulfilled.